A zero-dimensional topologically nontrivial state in a superconducting quantum dot - Marra, Pasquale; Braggio, Alessandro; Citro, Roberta (Beilstein Journal of Nanotechnology, 2018)
The classification of topological states of matter in terms of unitary symmetries and dimensionality predicts the existence of nontrivial topological states even in zero-dimensional systems, i.e., systems with a discrete energy spectrum. Here, we show that a quantum dot coupled with two superconducting leads can realize a nontrivial zero-dimensional topological superconductor with broken time-reversal symmetry, which corresponds to the finite size limit of the one-dimensional topological superconductor. Topological phase transitions corresponds to a change of the fermion parity, and to the presence of zero-energy modes and discontinuities in the current–phase relation at zero temperature. These fermion parity transitions therefore can be revealed by the current discontinuities or by a measure of the critical current at low temperatures.
Keywords: Josephson effect; Josephson junctions; quantum dots; superconducting quantum dots; topological states; topological superconductors

(untitled) - v. Klitzing, K.; Dorda, G.; Pepper, M. (Phys. Rev. Lett., 1980)

(untitled) - Thouless, D. J.; Kohmoto, M.; Nightingale, M. P.; den Nijs, M. (Phys. Rev. Lett., 1982)

(untitled) - Kitaev, A. Yu. (Phys.-Usp., 2001)

(untitled) - Hasan, M. Z.; Kane, C. L. (Rev. Mod. Phys., 2010)

(untitled) - Qi, X.-L.; Zhang, S.-C. (Rev. Mod. Phys., 2011)

(untitled) - Wehling, T. O.; Black-Schaffer, A. M.; Balatsky, A. V. (Adv. Phys., 2014)

(untitled) - Chiu, C.-K.; Teo, J. C. Y.; Schnyder, A. P.; Ryu, S. (Rev. Mod. Phys., 2016)

(untitled) - Altland, A.; Zirnbauer, M. R. (Phys. Rev. B, 1997)

(untitled) - Schnyder, A. P.; Ryu, S.; Furusaki, A.; Ludwig, A. W. W. (AIP Conf. Proc., 2009)

(untitled) - Kitaev, A. (AIP Conf. Proc., 2009)

(untitled) - Mourik, V.; Zuo, K.; Frolov, S. M.; Plissard, S. R.; Bakkers, E. P. A. M.; Kouwenhoven, L. P. (Science, 2012)

(untitled) - Nadj-Perge, S.; Drozdov, I. K.; Li, J.; Chen, H.; Jeon, S.; Seo, J.; MacDonald, A. H.; Bernevig, B. A.; Yazdani, A. (Science, 2014)

(untitled) - Pawlak, R.; Kisiel, M.; Klinovaja, J.; Meier, T.; Kawai, S.; Glatzel, T.; Loss, D.; Meyer, E. (npj Quantum Inf., 2016)

(untitled) - Alicea, J. (Rep. Prog. Phys., 2012)

(untitled) - Aguado, R. (Riv. Nuovo Cimento Soc. Ital. Fis., 2017)

(untitled) - Lutchyn, R. M.; Bakkers, E. P. A. M.; Kouwenhoven, L. P.; Krogstrup, P.; Marcus, C. M.; Oreg, Y. (Nat. Rev. Mater., 2018)

(untitled) - Sato, M.; Ando, Y. (Rep. Prog. Phys., 2017)

(untitled) - Leijnse, M.; Flensberg, K. (Semicond. Sci. Technol., 2012)

(untitled) - Elliott, S. R.; Franz, M. (Rev. Mod. Phys., 2015)

(untitled) - Beenakker, C. W. J. (Annu. Rev. Condens. Matter Phys., 2013)

(untitled) - Lutchyn, R. M.; Sau, J. D.; Das Sarma, S. (Phys. Rev. Lett., 2010)

(untitled) - Oreg, Y.; Refael, G.; von Oppen, F. (Phys. Rev. Lett., 2010)

(untitled) - Gangadharaiah, S.; Braunecker, B.; Simon, P.; Loss, D. (Phys. Rev. Lett., 2011)

(untitled) - Klinovaja, J.; Stano, P.; Loss, D. (Phys. Rev. Lett., 2012)

(untitled) - Klinovaja, J.; Stano, P.; Yazdani, A.; Loss, D. (Phys. Rev. Lett., 2013)

(untitled) - Jiang, L.; Pekker, D.; Alicea, J.; Refael, G.; Oreg, Y.; von Oppen, F. (Phys. Rev. Lett., 2011)

(untitled) - San-Jose, P.; Prada, E.; Aguado, R. (Phys. Rev. Lett., 2012)

(untitled) - Rokhinson, L. P.; Liu, X.; Furdyna, J. K. (Nat. Phys., 2012)

(untitled) - Brunetti, A.; Zazunov, A.; Kundu, A.; Egger, R. (Phys. Rev. B, 2013)

(untitled) - Chang, W.; Manucharyan, V. E.; Jespersen, T. S.; Nygård, J.; Marcus, C. M. (Phys. Rev. Lett., 2013)

(untitled) - Dolcini, F.; Houzet, M.; Meyer, J. S. (Phys. Rev. B, 2015)

(untitled) - Khanna, U.; Mukherjee, D. K.; Kundu, A.; Rao, S. (Phys. Rev. B, 2016)

(untitled) - Peng, Y.; Pientka, F.; Berg, E.; Oreg, Y.; von Oppen, F. (Phys. Rev. B, 2016)

(untitled) - Hussein, R.; Jaurigue, L.; Governale, M.; Braggio, A. (Phys. Rev. B, 2016)

(untitled) - Mellars, E.; Béri, B. (Phys. Rev. B, 2016)

(untitled) - Wiedenmann, J.; Bocquillon, E.; Deacon, R. S.; Hartinger, S.; Herrmann, O.; Klapwijk, T. M.; Maier, L.; Ames, C.; Brüne, C.; Gould, C.; Oiwa, A.; Ishibashi, K.; et al. (Nat. Commun., 2016)

(untitled) - Jellinggaard, A.; Grove-Rasmussen, K.; Madsen, M. H.; Nygård, J. (Phys. Rev. B, 2016)

(untitled) - Deacon, R. S.; Wiedenmann, J.; Bocquillon, E.; Domínguez, F.; Klapwijk, T. M.; Leubner, P.; Brüne, C.; Hankiewicz, E. M.; Tarucha, S.; Ishibashi, K.; Buhmann, H.; Molenkamp, L. W. (Phys. Rev. X, 2017)

(untitled) - Virtanen, P.; Bergeret, F. S.; Strambini, E.; Giazotto, F.; Braggio, A. (arXiv, 2017)

(untitled) - Mukherjee, D. K.; Rao, S.; Kundu, A. (Phys. Rev. B, 2017)

(untitled) - Khanna, U.; Rao, S.; Kundu, A. (Phys. Rev. B, 2017)

(untitled) - Pientka, F.; Keselman, A.; Berg, E.; Yacoby, A.; Stern, A.; Halperin, B. I. (Phys. Rev. X, 2017)

(untitled) - Huang, H.; Liang, Q.-F.; Yao, D.-X.; Wang, Z. (Phys. C (Amsterdam, Neth.), 2017)

(untitled) - Lee, E. J. H.; Jiang, X.; Žitko, R.; Aguado, R.; Lieber, C. M.; De Franceschi, S. (Phys. Rev. B, 2017)

(untitled) - Cayao, J.; San-Jose, P.; Black-Schaffer, A. M.; Aguado, R.; Prada, E. (Phys. Rev. B, 2017)

(untitled) - San-Jose, P.; Cayao, J.; Prada, E.; Aguado, R. (New J. Phys., 2013)

(untitled) - Cayao, J.; Black-Schaffer, A. M.; Prada, E.; Aguado, R. (Beilstein J. Nanotechnol., 2018)

(untitled) - Domínguez, F.; Kashuba, O.; Bocquillon, E.; Wiedenmann, J.; Deacon, R. S.; Klapwijk, T. M.; Platero, G.; Molenkamp, L. W.; Trauzettel, B.; Hankiewicz, E. M. (Phys. Rev. B, 2017)

(untitled) - Zyuzin, A.; Alidoust, M.; Loss, D. (Phys. Rev. B, 2016)

(untitled) - Marra, P.; Citro, R.; Braggio, A. (Phys. Rev. B, 2016)

(untitled) - Loss, D.; DiVincenzo, D. P. (Phys. Rev. A, 1998)

(untitled) - Choi, M.-S.; Bruder, C.; Loss, D. (Phys. Rev. B, 2000)

(untitled) - Kouwenhoven, L. P.; Austing, D. G.; Tarucha, S. (Rep. Prog. Phys., 2001)

(untitled) - van der Wiel, W. G.; Fujisawa, T.; Tarucha, S.; Kouwenhoven, L. P. (Jpn. J. Appl. Phys., 2001)

(untitled) - Tarasinski, B.; Chevallier, D.; Hutasoit, J. A.; Baxevanis, B.; Beenakker, C. W. J. (Phys. Rev. B, 2015)

(untitled) - Beenakker, C. W. J.; Edge, J. M.; Dahlhaus, J. P.; Pikulin, D. I.; Mi, S.; Wimmer, M. (Phys. Rev. Lett., 2013)

(untitled) - Stanescu, T. D.; Lutchyn, R. M.; Das Sarma, S. (Phys. Rev. B, 2013)

(untitled) - Lee, E. J. H.; Jiang, X.; Houzet, M.; Aguado, R.; Lieber, C. M.; De Franceschi, S. (Nat. Nanotechnol., 2013)

(untitled) - Yokoyama, T.; Eto, M.; Nazarov, Y. V. (J. Phys. Soc. Jpn., 2013)

(untitled) - Yokoyama, T.; Eto, M.; Nazarov, Y. V. (Phys. Rev. B, 2014)

(untitled) - Klees, R. L.; Rastelli, G.; Belzig, W. (Phys. Rev. B, 2017)

(untitled) - Li, Y.; Kundu, A.; Zhong, F.; Seradjeh, B. (Phys. Rev. B, 2014)

(untitled) - Benito, M.; Platero, G. (Phys. E (Amsterdam, Neth.), 2015)

(untitled) - Meng, T.; Florens, S.; Simon, P. (Phys. Rev. B, 2009)

(untitled) - Wentzell, N.; Florens, S.; Meng, T.; Meden, V.; Andergassen, S. (Phys. Rev. B, 2016)

(untitled) - Braggio, A.; Governale, M.; Pala, M. G.; König, J. (Solid State Commun., 2011)

(untitled) - Droste, S.; Andergassen, S.; Splettstoesser, J. (J. Phys.: Condens. Matter, 2012)

(untitled) - Hussein, R.; Braggio, A.; Governale, M. (Phys. Status Solidi B, 2017)

Quantum Transport: Introduction to Nanoscience - Nazarov, Y. V.; Blanter, Y. M. (Cambridge University Press, 2009)

(untitled) - Loring, T. A. (Ann. Phys., 2015)

(untitled) - Golubov, A. A.; Kupriyanov, M. Y.; Il’ichev, E. (Rev. Mod. Phys., 2004)

(untitled) - Tiira, J.; Strambini, E.; Amado, M.; Roddaro, S.; San-Jose, P.; Aguado, R.; Bergeret, F. S.; Ercolani, D.; Sorba, L.; Giazotto, F. (Nat. Commun., 2017)

(untitled) - Frolov, S. M.; Van Harlingen, D. J.; Oboznov, V. A.; Bolginov, V. V.; Ryazanov, V. V. (Phys. Rev. B, 2004)

(untitled) - Sochnikov, I.; Bestwick, A. J.; Williams, J. R.; Lippman, T. M.; Fisher, I. R.; Goldhaber-Gordon, D.; Kirtley, J. R.; Moler, K. A. (Nano Lett., 2013)

(untitled) - Szombati, D. B.; Nadj-Perge, S.; Car, D.; Plissard, S. R.; Bakkers, E. P. A. M.; Kouwenhoven, L. P. (Nat. Phys., 2016)

(untitled) - Ozyuzer, L.; Koshelev, A. E.; Kurter, C.; Gopalsami, N.; Li, Q.; Tachiki, M.; Kadowaki, K.; Yamamoto, T.; Minami, H.; Yamaguchi, H.; Tachiki, T.; Gray, K. E.; et al. (Science, 2007)

(untitled) - Solinas, P.; Gasparinetti, S.; Golubev, D.; Giazotto, F. (Sci. Rep., 2015)